Spark plasma sintered BaTiO3/graphene composites for thermoelectric applications. Issue 12 (September 2017) - Mallada, C.; Menéndez, J.L.; Dura, O.J.; López de la Torre, M.A.; Menéndez, R.; Santamaría, R.
Abstract: The viability of spark plasma sintered graphene/barium titanate ceramic matrix composites as thermoelectric materials is investigated. The temperature dependence of electrical conductivity, thermal conductivity and Seebeck coefficient was analyzed. The addition of low amounts of graphene oxide combined with the spark plasma sintering process increases electrical conductivity of pure BaTiO3 several orders of magnitude, whereas the thermal conductivity shows only a moderate enhancement. The composites display a semiconducting behaviour, with the resistivity decreasing with increasing temperature and following a thermally activated temperature dependence at high T. A strong dependence of ZT figure of merit with the graphene concentration and the measurement temperature was found. Optimal values are found for 1.7 wt% graphene oxide at the maximum experimental temperature (600 K).